Moralised Definitions of Freedom, Autonomy, and the Personal Value of Opportunities to Perform Morally Impermissible Actions - Intropi, Pietro (My University, 2021)
Are the opportunities to perform morally impermissible actions valuable? And, if so, has their value any role to play in normative arguments? In this essay I examine the personal value of opportunities to perform morally impermissible actions: the value that such opportunities have in virtue of contributing to someone’s autonomy and wellbeing. In particular, I discuss the relevance of the value of opportunities to perform morally impermissible actions for assessing moralised definitions of freedom in the context of an ethical system that appeals to axiological considerations, and I examine Raz’s account of the relationships between freedom and autonomy. Moralised definitions of freedom can be understood as claiming that only unobstructed opportunities to perform morally permissible actions should count as freedoms: I show that considerations concerning the personal value of the opportunities to perform morally impermissible actions underpin traditional critiques of moralised definitions and that emphasising this aspect allows to extend such critiques with new lines of argument. Furthermore, I discuss whether an argument recently advanced by Kramer can be framed as an internal critique of Raz’s account of the relationships between freedom and autonomy.
PUBLISHED
Keywords: Opportunity; Moralised freedom; Autonomy; Raz; Personal value